Evaluation of fluid dynamic oscillations by means of uRANS CFD methods - Gidda, Prabhakr Naidu. (2013)
Computational Fluid Dynamics (CFD) techniques are very viable and economical alternatives to experimental techniques in the present day world. They can offer much better insight into different aspects of the flow field which can never be achieved using experimental methods. In this thesis, a CFD analysis was carried out on flow over cavities of different sizes. It was found out that flow over cavities caused severe unsteady aerodynamic loading that resulted in various fluid oscillations within the cavity shear layer. These oscillations in turn caused severe unsteady pressure loading and noise radiation in various places like weapon bays in fighter aircrafts and in turbo machinery. The purpose of the thesis was to identify a few flow conditions where these oscillations occurred.